Gender Disparity in Awareness and Perception towards Novel Corona Virus (COVID-19) - Kaur, Manjot; Sharma, Preeti; Sidhu, Kiranjot (Indian Journal of Extension Education, 2025)
Cross sectional study was conducted to analyze the awareness and perception of male and female members of different sections of the society towards COVID-19 and the pandemic. The data complete in all respect of 339 respondents from twelve states was collected through online questionnaire which consisted of items to study awareness and perception was developed. Majority of the respondents were young and large majority were fully aware about the purpose of lockdown and the required response in terms of social isolation, quarantine and reporting of persons with travel history. They were also aware of the methods to check the spread of the virus, however, wearing face mask to avoid COVID-19 infection and check its spread was known to only half of the respondents.Â Highest per cent of the respondents, including both male and female strongly felt that government should invest more money into health care facilities to prevent future pandemics. It was concluded that highest percentage of the selected respondents had medium level of awareness but majority lacked awareness regarding some important aspects of COVID-Â 19, like its proneness of all age groups and days to show symptoms. Awareness regarding important aspects need to be created so as to correctly and scientifically perceive the issues pertaining to the virus and the pandemic.